Feasibility and Safety of Very-Low Contrast Combined Ringer's Solution in Optical Coherence Tomography Imaging - Chen, Tao; Yu, Huai; Ma, Lijia; Fang, Chao; Jia, Haibo; Liu, Huimin; Xu, Maoen; Zhang, Donghui; Yang, Guang; Zhang, Shuangyin; Han, Jincheng; Wei, Guo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Optical coherence tomography (OCT) is an important modality used in coronary intervention. However, OCT requires a high amount of contrast media, limiting its extensive application in clinical practice. This study compared OCT images of coronary lesions obtained using contrast media and very-low contrast combined Ringer’s solution (VLCCR) in patients with acute coronary syndrome (ACS). Methods: Thirty ACS patients with a total of 36 native lesions and stenoses from 70% to 90% were included in this study. Two kinds of flushing media (a contrast medium and VLCCR) were used in succession in a random order for OCT image pullback of each lesion. VLCCR method is using low volume contrast (4-5ml) injected into the guiding catheter previously combination with injector infused Ringer’s solution instead of pure contrast medium. The safety of procedure was evaluated by recording the patients ‘symptoms, changes of ECG, blood pressure and heart rate. OCT images were analyzed to determine the image clarity. Lumen area and diameter were also measured and the consistency between the two media was compared. Results: OCT procedure using either contrast or VLCCR did not show any peri-procedural adverse events. There was no difference in changes of blood pressure and heart rate in both procedures, however, VLCCR procedure showed less procedure-related symptoms and ECG changes. We found that the percentage of clear image frame was equivalent between the contrast and VLCCR media (98.0% vs. 96.9%, P = 0.90). We also observed a high degree of similarity between the different lesion phenotypes of ACS for both media. There was a linear correlation of the phenotypes obtained with these two different methods, and a significant correlation was observed between measurements obtained with contrast and VLCCR without correction for the refractive index of VLCCR (correlation coefficients ranged between 0.829 and 0.948). Conclusions: OCT imaging using VLCCR for blood clearance is feasible and safe and provides similar imaging quality compared to OCT imaging obtained using radiographic contrast media for ACS patients.